Solitaire - Oseman, Alice 1994- (HarperCollins Children's Books, 2018)
My name is Tori Spring. I like to sleep and I like to blog. Last year before all that stuff with Charlie and before I had to face the harsh realities of A-Levels and university applications and the fact that one day I really will have to start talking to people I had friends. Things were very different, I guess, but that's all over now. Now there's Solitaire. And Michael Holden. I don't know what Solitaire are trying to do, and I don't care about Michael Holden. I really don't. This incredible debut novel by outstanding young author Alice Oseman is perfect for fans of John Green, Rainbow Rowell and all unflinchingly honest writers.